Employee Engagement Mediating Self Efficacy and Quality of Work Life on Contact Center’s Burnout - Fulaedzah, Indah Asrin; Tjahjono, Heru Kurnianto; DA, Meika Kurnia Puji Rahayu (International Journal Labs, 2022)
Background: In the industrial revolution 4.0, there was a disruption of technology and innovation that led to major changes across the industrial sector and the service sector. The use of increasingly massive technology in various aspects gave rise to a new form of customer service that is systemized and integrated centrally or also referred to as a contact center (CC). Aim: The objective of this study is to test and analyze the role of employee engagement mediation in the influence of self efficacy and quality of work life (QWL) on burnout in contact centers (CC). Method: This study is a quantitative study with the research subject being a CC employee at one of the life insurance companies in Indonesia with as many as 137 respondents. Data analysis techniques use Structural Equation Modelling (SEM) with the help of AMOS applications. Findings: The results showed that the role of employee engagement in mediating the effect of self-efficacy on burnout was significant.